2002
DOI: 10.1055/s-2002-37403
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic Bacteria Associated with the Bryophyte Funaria hygrometrica: Effects of Methylobacterium Strains on Protonema Development

Abstract: Bacteria represent a substantial fraction of the microorganisms that inhabit leaf surfaces. We collected samples of the moss Funaria hygrometrica (L.) in the field and analysed the epiphytes on the gametophyte by the agar impression method and scanning electron/fluorescence microscopy. On the phylloid surface numerous bacteria were detected, notably in the grooves between adjacent lamina cells. Methanol‐ammonium salts agar surfaces impressed with isolated phylloids of green gametophytes resulted in the growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 17 publications
0
64
0
Order By: Relevance
“…Using a variety of biochemical and cytological methods, it has been shown that microbes of the genus Methylobacterium produced cytokinin (Koenig et al, 2002). The "classical" phytohormone auxin is also produced and secreted by different strains of Methylobacterium (Hornschuh et al, 2002). Basile et al, (1985) found that the PPFMs influence plant growth by production of phytohormones, such as IAA, cytokinins and vitamins.…”
Section: Impact Of Ppfm and Pgrs On Spad And Soluble Protein Contentmentioning
confidence: 99%
“…Using a variety of biochemical and cytological methods, it has been shown that microbes of the genus Methylobacterium produced cytokinin (Koenig et al, 2002). The "classical" phytohormone auxin is also produced and secreted by different strains of Methylobacterium (Hornschuh et al, 2002). Basile et al, (1985) found that the PPFMs influence plant growth by production of phytohormones, such as IAA, cytokinins and vitamins.…”
Section: Impact Of Ppfm and Pgrs On Spad And Soluble Protein Contentmentioning
confidence: 99%
“…4,8 the authors as PPFMs (see ref. 6), stimulated organ growth and reproductive development, compared with sterile controls. Based on these data, the authors proposed that a specific association between these microbial plant surface dwellers (PPFMs) and the liverwort may exist.…”
Section: Discussionmentioning
confidence: 95%
“…12 Numerous subsequent studies revealed that methylobacteria and bryophytes have, in the course of evolution, established a symbiotic relationship. [6][7][8] In their detailed study, Tani et al 3 document that bacterial strains that belong to the taxa M. adhaesivum, M. brachiatum, M. extorquens, M. marchantiae, M. komagatae and M. radiotolerans, and novel lineages close to M. adhaesivum, most of which were isolated from various bryophytes, are efficient colonizers of the phyllosphere. Based on these data, they speculate that microbes of the genus Methylobacterium preferentially colonize the above groundphytosphere of these "living fossil plants."…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phyllospheric microbes may perform an effective function in controlling the airborne pathogens inciting plant disease. Microbes on leaf surface are said to be extremophiles as they can tolerate low/high temperature (5-55°C) [15,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%